Up-Regulation of microRNA-34a in Women with Systemic Lupus Erythematosus - Abdullah, Wissam L.; Abed, Reema M. (Iraqi Journal of Science, 2024)
Systemic Lupus Erythematosus (SLE) is a chronic systemic autoimmune disease with multiple contributing factors. It is characterized by the immune system's inability to tolerate autoantigens such as nuclear antigens. The objective of this study is to evaluate the expression of microRNA-34a in relation to the incidence and occurrence of SLE in Iraqi women using quantitative real-time PCR and to determine its potential relationship with various demographic and laboratory parameters and disease activity. This investigation enrolled 100 healthy controls with a mean age of 31.68 years and 100 SLE patients, all of whom were women with a mean age of 32.85 years and  a disease duration of 9.00 (6.75) years. The mean of the Systemic Lupus Erythematosus disease activity index (SLEDAI-2k) score was 10.860±3.275. Erythrocyte sedimentation rate, C-reactive protein, urea, and creatinine were significantly higher (50.00 vs. 10.00 mm/h, 16.70 vs. 0.650 mg/dl, 58.00 vs. 33.00 mg/l, and 1.550 vs. 0.700 mg/l, respectively), while hemoglobin, white blood cells, and Complement 3 and Complement 4 were significantly lower (8.40 vs. 13.00 g/dl, 3.500 vs. 6.800 x 109  /L, 74.00 vs. 130.00 mg/dl, and 10.00 vs. 13.50 mg/dl, respectively) in patients with SLE compared with controls (P≤ 0.001). The analysis of anti-nuclear antibodies (ANA) in patients showed that 89% have ANA and 95% have anti-double-stranded DNA (anti-dsDNA). Also, the findings revealed a significant increase in microRNA-34a expression with fold change (5.19 ±0.48) when compared to the fold change mean in controls (1.00 ±0.00). There is no evidence for any correlation between microRNA-34a fold change and any laboratory or demographic examination of the illness in the present study except for age and BMI. In addition, receiver operating characteristic (ROC) analysis was performed on SLE patients to establish the diagnostic accuracy of microRNA-34a in differentiating SLE patients from controls. The specificity and sensitivity of microRNA-34a were 98% and 100%, respectively. The area under the curve (AUC) was 0.990, and the cutoff point was 1.050. This indicates that the identified microRNA-34a may represent strong biomarkers for SLE disorders.